Evaluation of growth and survival of vannamei shrimp (Litopenaeus vannamei) intensive system with probiotic supplementation in feed - Zubaidah, Anis; Lasmi, Huda; Hariyadi, Hariyadi (Acta Aquatica: Aquatic Sciences Journal, 2025)
The cultivation of vannamei shrimp (Litopenaeus vannamei) has become one of the most economically important sectors of aquaculture worldwide. However, challenges such as disease, declining water quality, and dependence on antibiotics have driven the search for more sustainable alternative solutions. The use of probiotics in feed has emerged as an innovative and environmentally friendly approach to improving shrimp health and production efficiency. Probiotics function by enhancing microbial balance in the digestive tract, strengthening the immune system, and improving nutrient absorption, which ultimately positively impacts the growth and survival of shrimp. This study highlights the importance of probiotic supplementation in shrimp feed cultivated under large-scale intensive systems. The method used in this study was an experimental method with two treatments: without probiotics (P0) and with probiotics (P1). The observed parameters included shrimp biomass growth (MBW), daily growth (SGR), and survival rate (SR). The results showed that the average MBW values were 8.83g (P0) and 8.92g (P1). The daily growth rate was 0.27%/day (P0) and 0.29%/day (P1). The FCR value was 1.2 for P0 and 0.9 for P1. Furthermore, the survival rate (SR) was 60% for P0 and 71% for P1. This study concludes that the use of probiotics in shrimp farming positively impacts the growth and survival of vannamei shrimp.Keywords: Effective; Lactobacillus Sp; Mortalities